Bioavilability of phosphorus from ammonium polyphosphate and single superphosphate in chicken - SINGH, DEVINDER; NAGRA, S S (The Indian Journal of Animal Sciences, 2013)
The bioavailability of phosphorus in ammonium poly phosphate (AP) and single superphosphate (SP) was determined in 2 feeding experiments using broiler chicks. Practical groundnut-cake, soybean-meal and maize-based diets with or without fish-meal supplementation were used. Body weight, tibia/toe weight and ash and tibia strength were the indices of measure. Feed grade dialcium phosphate (DCP) was used as the reference standard. The relative biological values (RBV) for phosphorus in AP were 93,97,95,91,95 and 99%, respectively, on the basis of body weight, toe weight/ash, tibia weight/ash and tibia strength against 100 for DCP. The respective values for SP were 74, 90, 86, 80, 70 ans 96%. The phosphorus retention from AP and SP on balance has is was 79.4 and 76.0% as against 81.9% from DCP. The combined use of AP or SP with DCP had no synergistic effect on the bioavailability of phosphorus.